2013
DOI: 10.4111/kju.2013.54.5.289
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Randomized Controlled Urological Trials Conducted by Korean Medical Institutions

Abstract: PurposeTo assess the quality of randomized controlled urological trials conducted by Korean medical institutions.Materials and MethodsQuality assessment was conducted by using the Jadad scale; in addition, the van Tulder scale and the Cochrane Collaboration risk of bias tool were used as individual indices. All assessments were performed by two reviewers. If the outcomes differed, the two reviewers and a third reviewer adjusted the discrepancy in the results through discussion. Starting from 1986, a quality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 18 publications
2
48
0
Order By: Relevance
“…The assessment assigns a judgment of “yes,” “no,” or “unclear” for each domain to designate a low, high, or unclear risk of bias respectively. The study having a low risk of bias was determined if one or no domain was considered or labeled “unclear” or “no.” The study was classified as having a high risk of bias contained four or more domains and was considered or labeled “unclear” or “no” (Chung & Lee, ). The quality of the current study and publication bias were evaluated by Review Manager 5 (RevMan 5.2.3, Cochrane Collaboration, and Oxford, UK).…”
Section: Methodsmentioning
confidence: 99%
“…The assessment assigns a judgment of “yes,” “no,” or “unclear” for each domain to designate a low, high, or unclear risk of bias respectively. The study having a low risk of bias was determined if one or no domain was considered or labeled “unclear” or “no.” The study was classified as having a high risk of bias contained four or more domains and was considered or labeled “unclear” or “no” (Chung & Lee, ). The quality of the current study and publication bias were evaluated by Review Manager 5 (RevMan 5.2.3, Cochrane Collaboration, and Oxford, UK).…”
Section: Methodsmentioning
confidence: 99%
“…The study showed a high risk of bias if 4 or more domains were regarded as "unclear" or "no." 19 Quality evaluation and investigation of risk of bias were performed using Review Manager 5 (RevMan 5.2.3; Cochrane Collaboration, Oxford, United Kingdom).…”
Section: Data Extraction and Quality Evaluationmentioning
confidence: 99%
“…When four or more aspects are deemed “unclear” or “no,” the study has a high risk of bias. If two or three aspects are deemed “unclear” or “no,” the study has a moderate risk of bias [22]. Quality assessment of publication bias was performed by Review Manager 5 (RevMan 5.2.3, Cochrane Collaboration, Oxford, UK).…”
Section: Methodsmentioning
confidence: 99%